A taxonomic monograph of the genus Dodomeira Bellò & Baviera, a new genus of Peritelini from Sicily (Coleoptera: Curculionidae: Entiminae) - Bello, Cesare; Osella, Giuseppe; Baviera, Cosimo (Zootaxa, 2017)
The genus Dodomeira Bellò & Baviera gen. n. of the tribe Peritelini Lacordaire (1863) (Curculionidae: Entiminae) which includes 39 species is described. Seven species are transferred from Pseudomeira Stierlin, 1881: Dodomeira confusa (Pierotti, 2012) comb. n., Dodomeira exigua (Stierlin, 1861) comb. n., Dodomeira ficuzzensis (Bellò & Baviera, 2011) comb. n., Dodomeira himerensis (Bellò & Baviera, 2011) comb. n., Dodomeira petrensis (Bellò & Baviera, 2011) comb. n., Dodomeira pfisteri (Stierlin, 1864) comb. n., Dodomeira trinacriae (Bellò & Baviera, 2011) comb. n.. Thirty-two species are new for science and here described: Dodomeira adrianae Bellò & Baviera sp. n., Dodomeira alta Bellò & Baviera sp. n., Dodomeira angelae Bellò & Baviera sp. n., Dodomeira asinelliensis Bellò & Baviera sp. n., Dodomeira belicensis Bellò & Baviera sp. n., Dodomeira bertoni Bellò & Baviera sp. n., Dodomeira calatina Bellò & Baviera sp. n., Dodomeira caoduroi Bellò & Baviera sp. n. n., Dodomeira elima Bellò & Baviera sp. n., Dodomeira enzoi Bellò & Baviera sp. n., Dodomeira fossor Bellò & Baviera sp. n., Dodomeira forbicionii Bellò & Baviera sp. n., Dodomeira genistae Bellò & Baviera sp. n., Dodomeira giustoi Bellò & Baviera sp. n., Dodomeira hiemalis Bellò & Baviera sp. n., Dodomeira ibleiensis Bellò & Baviera sp. n., Dodomeira illuminatae Bellò & Baviera sp. n., Dodomeira juliae Bellò & Baviera sp. n., Dodomeira laliaensis Bellò & Baviera sp. n., Dodomeira magrinii Bellò & Baviera sp. n., Dodomeira montivaga Bellò & Baviera sp. n., Dodomeira margheritae Bellò & Baviera sp. n., Dodomeira maritimaensis Bellò & Baviera sp. n., Dodomeira nobilis Bellò & Baviera sp. n., Dodomeira paladinii Bellò & Baviera sp. n., Dodomeira sabellai Bellò & Baviera sp. n., Dodomeira saccoi Bellò & Baviera sp. n., Dodomeira sicana Bellò & Baviera sp. n., Dodomeira sicelidis Bellò & Baviera sp. n., Dodomeira siderea Bellò & Baviera sp. n., Dodomeira silvanae Bellò & Baviera sp. n., Dodomeira zingara Bellò & Baviera sp. n.. In addition, according to morphological characters, eight informal groups of species are established (the number of species ascribed to the group is in brackets): Dodomeira adrianae species group (13), Dodomeira caoduroi species group (2), Dodomeira exigua species group (5), Dodomeira ficuzzensis species group (2), Dodomeira maritimaensis species group (1), Dodomeira petrensis species group (2), Dodomeira pfisteri species group (13), Dodomeira saccoi species group (1). We present a key for the identification of the new genus among Palaearctic Peritelini, one for single species groups and an other for each species. A checklist of all the species currently known of Dodomeira gen. n. and Pseudomeira Stierlin (1881), with distribution maps and data on ecology and phenology of all the species of Dodomeira gen. n. are also provided.